Effectiveness of physical activity on patients with depression and Parkinson's disease: A systematic review. - Pei-Ling Wu; Megan Lee; Tzu-Ting Huang (PLoS ONE)
Aim In this paper we aimed to systematically review the literature on physical activity's effect on depressive symptoms in Parkinson disease. Background Depression is a common symptom of Parkinson's disease and is associated with increased disability, rapid progression of motor symptoms, mortality, and adverse effects on Quality of Life. Design A systematic review of primary research was undertaken and conducted according to the Preferred Reporting Items for Systematic Reviews. Data sources Databases Scopus, Psycho-info, CINAHL, PubMed, and ProQuest Cochrance were searched from January 2006 to June 2017. The language was restricted to English. Review methods Abstracts were screened and reviewed against the eligibility criteria (participants' mean age were ≥ 60 with PD, PA interventions, depression as one of outcome variables, and Randomized Control Trail or quasi-experimental design). Two reviewers appraised the quality of the data extracted. The modified Jadad scale assessed the quality of the methodology of the published papers. Results The database search yielded 769 abstracts, 11 of which were included in this review and awarded scores ranging from 3 to 8 (Scale scores range from 0 to 8 points, higher scores indicated better quality) by the raters. These 11 studies included 342 patients and executed 17 kinds of physical activity programs. Results of this review show empirical evidence to support the efficacy of physical activity for the population with Parkinson's disease. Aerobic training exercise significantly improved the participants' scores on the Unified Parkinson's Disease Rating Scale, the Beck Depression Inventory, and the Quality of Life of the patients. Qigong improved scores in UPDRS-III and decreased incidences of multiple non-motor symptoms and depression. Furthermore, a balance-training program, such as Tai Chi, can improve postural stability and Quality of Life. Conclusions Physical activity may assuage the degeneration of motor skills and depression as well as increase the Quality of Life of Parkinson's disease patients, with aerobic training producing the best results. These findings suggest that physical activity, notably aerobic training, could be a good exercise strategy for patients with Parkinson's disease.